2021
DOI: 10.20885/jkki.vol12.iss3.art8
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Propolis Terhadap Ekspresi BDNF Di Hippocampus Tikus Yang Diinduksi Stres

Abstract: Latar belakang: Brain-derived neurotrophic factor (BDNF) merupakan neurotrophin yang disekresi oleh dendrit. BDNF berperan pada diferensiasi, maturasi dan menjaga survival neuron. BDNF juga berperan penting pada neuroplastisitas, learning and memory. Ekspresi BDNF menurun pada kondisi stres. Propolis mengandung chyrisin yang memiliki efek antioksidan dan neuroprotektan. Penelitian ini ingin melihat efek propolis terhadap ekspresi BDNF pada hippocampus tikus yang diinduksi stres.Tujuan: untuk mengetahui pengaru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(12) This study showed through qRT-PCR analysis that the group receiving South Sulawesi propolis at a dose of 1 μg/mL expressed BDNF mRNA significantly higher than did the medium group. In a study by Kuswati et al (22) using rats that had previously experienced induced stress for 14 days, it was found that BDNF expression in the hippocampus was significantly higher in the group given propolis at a dose of 200 mg/kgBW compared to those not given propolis. The latter study is in line with our study which showed that BDNF mRNA expression in the group given propolis was higher than that in the medium group as a positive control.…”
Section: Discussionmentioning
confidence: 98%
“…(12) This study showed through qRT-PCR analysis that the group receiving South Sulawesi propolis at a dose of 1 μg/mL expressed BDNF mRNA significantly higher than did the medium group. In a study by Kuswati et al (22) using rats that had previously experienced induced stress for 14 days, it was found that BDNF expression in the hippocampus was significantly higher in the group given propolis at a dose of 200 mg/kgBW compared to those not given propolis. The latter study is in line with our study which showed that BDNF mRNA expression in the group given propolis was higher than that in the medium group as a positive control.…”
Section: Discussionmentioning
confidence: 98%